Uso de doppler colorido na avaliação funcional do corpo lúteo em bovinos - Arêas, Vagner Sarmento (2012)
The aim of the present study was to evaluate the luteal vascular pattern between days 12 and 20 post insemination, and to establish the accuracy of the use of color Doppler in predicting non-pregnancy 20 days after fixed time artificial insemination (FTAI), using as a single parameter the visual evaluation of corpus luteum blood flow (CLBF). Crossbred Holstein x Gyr cows and heifers, undergoing two FTAI protocols, were used. In the first study, animals (n=115) were monitored between days 12 and 20 after the first FTAI, and corpora lutea (CL) evaluated every 48h using a portable ultrasound device equipped with color Doppler function (MyLab30, Esaote, Italy) and a 7.5 MHz linear rectal probe. The total CL area (TCLA), luteal cavity area (LCA), luteal tissue area (LTA, TCLA minus LCA, if present), Doppler signal area (DSA) and proportion DSA:LTA (PDL). Pregnancy diagnosis was performed on Day 30 (D30), 9 Luteal activity was monitored by plasma progesterone concentration (PPC) in samples colected in the same days of the ultrasound exams. The values of TCLA, LCA, LTA, DSA and PDL from D12 to D20 were compared between animals later diagnosed as pregnant or non-pregnant. There was no day effect on TCLA, LCA, LTA, DSA or PDL in animals later diagnosed as pregnant (P>0.05). In non-pregnant animals, there was a reduction (P<0.01) in all luteal parameters up to D20. Despite of the high VCs of Doppler measures (DSA and PDL), differences between pregnant and non-pregnant animals were detected earlier than in LTA (from D18), the PPC (D18) and CLA (D20). In the second experiment, evaluations (n=208) were performed in the animals in the two sessions of FTAI, on Day 20 (D20) after insemination. Luteal blood flow was evaluated using color Doppler ultrasonography, as previously described. Considering only the visual and subjective evaluation of CLBF the animals were classified as ‘pregnant’ or ‘non pregnant’. Pregnancy diagnose was performed on D30, by the same technician, and retrospectively compared to the presumptive diagnose based in CLBF and result classified as correct or incorrect. The number of true-positive (TP), true-negative (TN), false positive (FP) and false-negative (FN) were compared in a contingency table 2x2. The sensibility (SEN), specificity (SPEC), positive predictive value (PPV), negative predictive value (NPV) and accuracy (ACC) in the diagnose by CLBF were calculated as follows: SEN=TP/(TP+FN); ESP=TN/(FP+TN); PPV=TP/(TP+FP); NPV=TN/(FN+TN); and ACC=(TP+TN)/n. Pregnancy rate and proportions were analyzed by Chi-square. Overall performance of the presumptive diagnose based on CLBF was: SEN=97.1%; SPEC=51.9%; PPV=66.9%; PNV=94.7%; and ACC=74.5%. The proportion of FP was 24.0% (50/208) and of FN 1.4% (3/208). In conclusion, the use of color Doppler provides earlier and more acurate diagnostics of luteal function in the pregnancy recognition period; and the visual evaluation of CLBF 20 days after FTAI can be used to identify and select non-pregnant animals for resynchronization.